PENGEMBANGAN ALAT PERAGA ELEKTROLISER SEDERHANA SEBAGAI MEDIA PEMBELAJARAN HUKUM I TERMODINAMIKA - Didik Rahmadi; Kartini Herlina; Hervin Maulina; Doni Andra (Universitas Sriwijaya, 2021)
This development research aims to test the validity of the simple electrolyzer props on the first law of thermodynamics, to describe the attractiveness, practicality, and usefulness of the simple electrolyzer props on the first law of thermodynamics. This development research uses the Design and Development Reaserch (DDR) approach with data analysis techniques using an assessment of validity test data and practicality test data consisting of observance assessment data, student response data, and teacher perception data. The results of this study indicate that the validity test of the developed teaching aids is categorized as very valid. The results of students responses were categorized as good, and the results of teachers' perceptions were categorized as good.